Sculpté, gravé, peint, moulé, estampé - Alain Fretz; Stephan Gasser (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
In the scope of a joint research project by the University and the Museum of Art and History of Fribourg dedicated to the study of local sculpture production in the 16th century, up to 460 altarpieces, reliefs and single sculptures have been examined by a research group. On behalf of chosen examples, the article describes the methods and techniques used by medieval sculptors and painters to imitate textile. It also submits evidence of the phenomenon of applied decorations in relief made of stamped paper found sporadically within the examined corpus alongside with the traditional applied brocade made of tin foil.